Differential expression of microRNAs contributed to the health efficacy of EGCG in in vitro subarachnoid hemorrhage model. Issue 12 (21st November 2017) - Chen, Ying; Huang, Liyong; Wang, Lei; Chen, Lingyun; Ren, Wenhua; Zhou, Wenke
Abstract : (1) EGCG prevented miRNA dysregulation after SAH; (2) multi-target mechanisms of EGCG might rely on its regulatory roles on miRNAs expression, such as those miRNAs targeting p38, Ca 2+, and autophagic activation; (3) the differential expression of miRNAs might determine the therapeutic efficacy of different concentration of EGCG. Abstract : (−)-Epigallocatechin-3-gallate (EGCG) exhibits a broader spectrum health efficacy in subarachnoid hemorrhage (SAH) therapy; the mechanisms, however, are largely unknown. Given that miRNAs play important roles in regulation of thousands of gene expressions, the effect of EGCG on the expression of miRNAs was investigated to explore the multi-targeting actions of EGCG by using an in vitro SAH model. MTT and western blot assays were used to assess the health effects of EGCG in SAH progression; the results showed that oxyhemoglobin (OxyHb)-induced cell proliferation and excessive autophagic activation were significantly inhibited by 50 μM EGCG, but not by 1 μM EGCG. By high throughput sequencing analysis, the miRNA profiles of normal, SAH and EGCG (1 and 50 μM) groups were compared and a total of 953 miRNAs were identified. Of 192 differentially expressed miRNAs, 43 miRNAs were significantly differentially expressed in SAH ( p < 0.01). However, EGCG significantly increased the number of differential expressions of miRNAs, which showed 144 and 138 miRNAs (112 and 115 upregulated, 32 and 23 downregulated, p < 0.01) in 1 μM and 50 μM EGCG groups, respectively. Among all the differentially expressed miRNAs, 13 miRNAs were shared by the three groups. 5 miRNAs (miR-218-5p, miR-218b, miR-143-3p, miR-101a-3p, miR-30a-3p) were detected in both SAH and EGCG 1 μM groups, and 104 miRNAs were shared by the EGCG 1 μM and EGCG 50 μM groups. Only 1 miRNA (miR-532-5p) was discovered in both SAH and EGCG 50 μM groups. Moreover, 24, 22 and 20 specific differentially expressed miRNAs were discovered in SAH, 1 μM and 50 μM EGCG groups, respectively. The predicted target genes of differentially expressed miRNAs showed that the most impacted MAPK signaling pathway, particularly the upregulated p38 expression in the SAH group, was restored to the normal level in both EGCG groups, but the calcium signaling pathway was enriched only in the EGCG 50 μM group. These results revealed that differential expression of miRNAs is fundamental to understand the multiple targets actions of EGCG in SAH therapy, and simultaneously targeting more robust signaling pathways could determine the therapeutic effects of EGCG.